Derivative Financial Instruments: Concept, Operation, and Trading Strategies - Mesén Figueroa, Vernor (2008)
The derivatives grow to be one of the most polished financial instruments during the past few years, therefore our interest in this subject. A derivative is a financial instrument tied to the value of underlying assets, such as commodities, stock options, bonus, interest rates, and currencies, among others. Different types of derivatives exist, among them: futures, forwards, options and swaps. These instruments are negotiated as well in organized markets as in unorganized markets, more commonly known as OTC (over the Counter) and commonly used as cover instrument or speculation. This article attempts to approach the reader to this concept: its characteristics, types, procedure and strategies.